Nitric oxide synthase inhibition results in synergistic anti-tumour activity with melphalan and tumour necrosis factor alpha-based isolated limb perfusions - de Wilt, J H W (Nature Publishing Group, 2000)
Nitric oxide (NO) is an important molecule in regulating tumour blood flow and stimulating tumour angiogenesis. Inhibition of NO synthase by L-NAME might induce an anti-tumour effect by limiting nutrients and oxygen to reach tumour tissue or affecting vascular growth. The anti-tumour effect of L-NAME after systemic administration was studied in a renal subcapsular CC531 adenocarcinoma model in rats. Moreover, regional administration of L-NAME, in combination with TNF and melphalan, was studied in an isolated limb perfusion (ILP) model using BN175 soft-tissue sarcomas. Systemic treatment with L-NAME inhibited growth of adenocarcinoma significantly but was accompanied by impaired renal function. In ILP, reduced tumour growth was observed when L-NAME was used alone. In combination with TNF or melphalan, L-NAME increased response rates significantly compared to perfusions without L-NAME (0–64% and 0–63% respectively). An additional anti-tumour effect was demonstrated when L-NAME was added to the synergistic combination of melphalan and TNF (responses increased from 70 to 100%). Inhibition of NO synthase reduces tumour growth both after systemic and regional (ILP) treatment. A synergistic anti-tumour effect of L-NAME is observed in combination with melphalan and/or TNF using ILP. These results indicate a possible role of L-NAME for the treatment of solid tumours in a systemic or regional setting. © 2000 Cancer Research Campaign